1997
DOI: 10.1002/(sici)1097-0126(199706)43:2<143::aid-pi717>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Opaque Methacrylate Polymers for Biomedical Applications

Abstract: The synthesis of a number of halogenated aromatic methacrylate monomers was achieved by (1) the esterification of hydroxyl‐containing methacrylate esters with 2,3,5‐tri‐iodobenzoic acid and (2) by the nucleophilic addition of 2,3,5‐tri‐iodobenzoic acid, or polyhalogenated phenols, to 2,3‐epoxypropyl methacrylate, yielding white crystalline products which were fully characterized. These monomers could be homopolymerized in the melt to produce clear, intensely X‐ray opaque glasses possessing high refractive indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 3 publications
0
64
0
Order By: Relevance
“…One well-known solution, especially in the case of dental and bone cements, is the incorporation of inorganic additives, such as barium sulphate or zirconium dioxide particles. In the case of methacrylic bone cements, it has been reported that these particles diminish the mechanical properties (especially fatigue life) due to the creation of interfaces between the polymeric matrix and the inorganic radio-opacifying particles [1,[7][8][9][10][11][12]. In addition, the release of such particles has been found to be deleterious to bone since they activate bone resorption [13].…”
Section: Introductionmentioning
confidence: 99%
“…One well-known solution, especially in the case of dental and bone cements, is the incorporation of inorganic additives, such as barium sulphate or zirconium dioxide particles. In the case of methacrylic bone cements, it has been reported that these particles diminish the mechanical properties (especially fatigue life) due to the creation of interfaces between the polymeric matrix and the inorganic radio-opacifying particles [1,[7][8][9][10][11][12]. In addition, the release of such particles has been found to be deleterious to bone since they activate bone resorption [13].…”
Section: Introductionmentioning
confidence: 99%
“…It means that Bis-GMA behaviors like supramolecules because of intermolecular association stemmed from hydrogen bonding between Bis-GMA molecules. [20][21][22][23][24][25] High viscosity of Bis-GMA is abruptly decreased from 574 to 0.4-3.7 Pa.s by substituting alkoxy groups for hydroxyl groups in Bis-GMA. The viscosities of the organic monomers were gradually decreased by increasing their substituent size.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Bis-GMA alternatives with lower viscosities, such as dimethacrylate monomers of propoxylated-diphenol, silylated Bis-GMA alternatives, and ethoxy and methyl siloxy analogues of Bis-GMA, have been examined to reduce or eliminate the inclusion of diluent to the resin matrix. [21][22][23][24][25][26] However, these Bis-GMA alternatives still required small amount of TEGDMA since the viscosity was higher than commercially available organic matrix. In the previous studies, we had also developed Bis-GMA alternatives having low viscosity by replacing hydroxyl groups in Bis-GMA with alkoxy groups.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this incompatibility with the polymeric matrix, the contrast forms a segregated phase and makes mixing of reagents more difficult during the preparation. For this reason, some authors have suggested the use of alternative contrasts, such as iodine (Almén, 1995;Davy et al, 1997;Davenport et al, 1999;Ginebra et al, 2002;Nakamura et al, 2003;Artola et al, 2004;Kjellson et al, 2004;Van Hooy-Corstjensa et al, 2004) and/or bismuth (Rawls et al, 1996;Deb et al, 2002) based compounds. These compounds are chemically linked to specially designed monomers and are thus automatically incorporated into the BC formulation.…”
Section: Verified That It Is Verymentioning
confidence: 99%